Pengaruh Hedonic Shopping Motivation, Shopping Lifestyle dan Fashion Involvement Terhadap Impulse Buying Pada Pelanggan Zalora Di Kota Medan - Myisha Nevianda Tuzzahra; Satria Tirtayasa (Fisarrearch, 2020)
The purpose of this research is to analyse the direct influence of Hedonic Shopping Motivation, Shopping Lifestyle dan Fashion Involvement against Impulse Buying. The population of this research is Zalora's customer in Medan. With the population unknown, it uses Bernoulli formula and a sample number of 96 respondents with purposive sampling. Data is obtained by Google form questionnaire. The data analysis method used is associative statistical analysis and Partial-Least Square analysis (SEM-PLS). The analysis is assisted with Smart PLS 3.0 program. Data analysis techniques use multiple linear regression, realibilty and validity tests, R-Square, T-Test, F-Test. The results showed that the Hedonic Shopping Motivation variable had significant effect on Impulse Buying, the Shopping Lifestyle variable has significant effect on Impulse Buying and the Involvement Fashion variable has significant effect on Impulse Buying.